Small Ubiquitin-Like Modifier 4 (SUMO4) Gene M55V Polymorphism and Type 2 Diabetes Mellitus: A Meta-analysis Including 6,823 Subjects - Li, Yan-yan; Wang, Hui; Yang, Xin-xing; Geng, Hong-yu; Gong, Ge; Kim, Hyun Jun; Zhou, Yan-hong; Wu, Jing-jing (Frontiers in Endocrinology, 2017)
Background: Many studies suggest that the small ubiquitin-like modifier 4 (SUMO4) M55V gene polymorphism (rs237025) may be associated with an increased risk of type 2 diabetes mellitus (T2DM). However, due to other conflicting results, a clear consensus is lacking in the matter. Objective and methods: A meta-analysis consisting of 6,823 subjects from 10 studies was conducted to elucidate relationship between the SUMO4 M55V gene polymorphism and T2DM. Depending on the heterogeneity of the data, either a fixed or random-effects model would be used to assess the combined odds ratio (ORs) and their corresponding 95% confidence interval (CI). Results: SUMO4 gene M55V polymorphism was significantly associated with T2DM in the whole population under allelic (OR: 1.18, 95% CI: 1.10 - 1.28, P = 1.63×10-5), recessive (OR: 1.59, 95% CI: 1.14-2.23, P = 0.006), dominant (OR: 0.815, 95% CI: 0.737 - 0.901, P = 6.89×10-5), homozygous (OR: 1.415, 95% CI: 1.170 - 1.710, P = 0.0003), heterozygous (OR: 1.191, 95% CI: 1.072 - 1.323, P = 0.001), and additive genetic models (OR: 1.184, 95% CI: 1.097 - 1.279, P = 1.63×10-5). In our subgroup analysis, a significant association was found again in the Chinese population, but not in Japanese or Iranian population. Conclusion: SUMO4 gene M55V polymorphism may correlate with increased T2DM risk. Chinese carriers of the V allele of the SUMO4 gene M55V polymorphism may be predisposed to developing T2DM.